1993
DOI: 10.1084/jem.178.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 4 reverses T cell proliferative unresponsiveness and prevents the onset of diabetes in nonobese diabetic mice.

Abstract: SummaryBeginning at the time of insulitis (7 wk of age), CD4 + and CD8 + mature thymocytes from nonobese diabetic (NOD) mice exhibit a proliferative unresponsiveness in vitro after T cell receptor (TCR) crosslinking. This unresponsiveness does not result from either insulitis or thymic involution and is long lasting, i.e., persists until diabetes onset (24 wk of age). We previously proposed that it represents a form of thymic T cell anergy that predisposes to diabetes onset. This hypothesis was tested in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
269
3
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(288 citation statements)
references
References 54 publications
(53 reference statements)
14
269
3
2
Order By: Relevance
“…IL-4 may be important in the maintenance of a protective Th2 response [5], but it has also been implicated in the stimulation of a broader T cell repertoire composed of non-pathogenic cells [6] and in differential expression of B7.1 and B7.2 molecules by DCs, affecting the quality of CTL responses [7]. Systemic administration of IL-4 appeared to alleviate a form of unresponsiveness among NOD thymocytes and peripheral T cells, which correlated with disease protection [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-4 may be important in the maintenance of a protective Th2 response [5], but it has also been implicated in the stimulation of a broader T cell repertoire composed of non-pathogenic cells [6] and in differential expression of B7.1 and B7.2 molecules by DCs, affecting the quality of CTL responses [7]. Systemic administration of IL-4 appeared to alleviate a form of unresponsiveness among NOD thymocytes and peripheral T cells, which correlated with disease protection [8].…”
Section: Introductionmentioning
confidence: 99%
“…Systemic IL-4 administration, via regular intraperitoneal injections [5,8,22], gene gunor carrier-mediated DNA delivery [23,24] or IL-4-encoding adenoviral vectors [25], prevented T1D when NOD mice were treated at a young age (up to 7 weeks). At the level of cellular gene therapy, IL-4-expressing transduced T cells [26,27] or dendritic cells (DCs) [28] have been used with some success.…”
Section: Introductionmentioning
confidence: 99%
“…Autoimmunity in NOD mice is T cell-dependent [1,2], and a role for the thymus has been evoked. Specific deficiency in thymic NKT cells is relevant to the immunopathology seen in this mouse [6,7]; NOD thymocytes produce low amounts of IL-4 [8], respond poorly to cytokines [9] and are relatively insensitive to apoptotic signals [10,11]. Experiments with F1 chimeras showed that the hemopoietic-derived thymic microenvironment is essential for development of diabetes [12,13] and intrathymic injection of Langerhans' islets abrogates autoimmunity [14].…”
Section: Introductionmentioning
confidence: 99%
“…22,23,[30][31][32][68][69][70][71][72] The current study demonstrates, for the first time, the appearance of 'natural' antiself antibodies to a key pro-inflammatory cytokine, TNF-␣, during the development of a T cell-mediated autoimmune disease of the CNS. These antibodies developed in rats immunized with p68-86/CFA and not with the CFA alone (Figure 3), even though both groups exhibited an extensive local inflammatory process at the site of CFA immunization.…”
Section: Figure 6 Tnf-␣-specific Antibodies Produced By Dna Vaccinatimentioning
confidence: 66%
“…[12][13][14][15][16][17][18][19][20][21] Th1 cells selected in response to various autoantigens transfer T cell-mediated autoimmune diseases, whereas IL-4-secreting Th2 cells, selected in response to these same antigens, either inhibit or exert no profound effect on the inflammatory process. 16,[22][23][24][25][26][27][28][29][30][31][32][33][34] High levels of IFN-␥ and low levels of IL-4 positively select for Th1 cells, whereas low levels of IFN-␥ together with high levels of IL-4 mediate Th2 selection. [12][13][14][15][16][17] In a recent study, we isolated mRNA encoding interferon gamma-inducing factor (IGIF, IL-18) from the EAE brain, generated neutralizing antibodies against its gene product and explored the critical role of IGIF in T cell selection and regulation of disease.…”
Section: Introductionmentioning
confidence: 99%